2020
DOI: 10.1111/eci.13468
|View full text |Cite
|
Sign up to set email alerts
|

Association of beta‐hydroxybutyrate with development of heart failure: Sex differences in a Dutch population cohort

Abstract: Background: In the failing heart, energy metabolism is shifted towards increased ketone body oxidation. Nevertheless, the association of beta-hydroxybutyrate (β-OHB) with development of heart failure (HF) remains unclear. We investigated the association between plasma β-OHB and the risk of HF in a prospective populationbased cohort. Design: Plasma β-OHB concentrations were measured in 6134 participants of the PREVEND study. Risk of incident HF with reduced (HFrEF) or preserved (HFpEF) ejection fraction was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
(72 reference statements)
2
32
0
Order By: Relevance
“…Circulating ketone body concentrations were increased in patients with heart failure, in correlation with cardiac use. The concentrations of βOHB in circulation were also increased in persons with incident heart failure [115]. Circulating levels of ketone bodies and their myocardial use were also found increased in persons with type 2 diabetes [14].…”
Section: (Pre)clinical Experience With Supplementation Of Ketone Bodiesmentioning
confidence: 93%
“…Circulating ketone body concentrations were increased in patients with heart failure, in correlation with cardiac use. The concentrations of βOHB in circulation were also increased in persons with incident heart failure [115]. Circulating levels of ketone bodies and their myocardial use were also found increased in persons with type 2 diabetes [14].…”
Section: (Pre)clinical Experience With Supplementation Of Ketone Bodiesmentioning
confidence: 93%
“…One showed similar levels of N-terminal pro-BNP [ 6 ] between men and women, whilst another study showed women tended to have a higher BNP [ 26 ]. Although the implications are unknown currently, one paper discovered that high plasma concentrations of beta hydroxybuturate were associated with increased risk of HFrEF particularly in women [ 27 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…We found values higher than normal for nine TTS patients, reaching a maximum of almost 3 mM in 3HB and 1 mM in AcAc. In contrast, healthy subjects show concentrations of KB as low as 19 μM, which can increase to approximately 120 μM after an overnight fast [ 38 ]. Our TTS patients were studied in the nonfasting state upon admission, thereby enhancing the significance of the high KB levels observed.…”
Section: Discussionmentioning
confidence: 99%